Textbook on international human rights - Smith, Rhona K. M. (Oxford University Press, 2014)
Global in coverage, the sixth edition of Textbook on International Human Rights provides a concise, wide-ranging introduction for law students new to the subject. It considers historical factors, the work of the UN, regional systems, and a variety of substantive rights